Tokens and social life in Roman imperial Italy - Rowan, Clare, 1982- (Cambridge University Press, 2023)
Tokens are underutilised artefacts from the ancient world, but as everyday objects they were key in mediating human interactions. This book provides an accessible introduction to tokens from Roman Italy. It explores their role in the creation of imperial imagery, as well as what they can reveal about the numerous identities that existed in different communities within Rome and Ostia. It is clear that tokens carried imagery that was connected to the emotions and experiences of different festivals, and that they were designed to act upon their users to provoke particular reactions. Tokens bear many similarities to ancient Roman currency, but also possess important differences. The tokens of Roman Italy were objects used by a wide variety of groups for particular events or moments in time; their designs reveal experiences and individuals otherwise lost to history. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 07 Nov 2023).
Keywords: Tokens -- Rome -- History.; Rome -- Social life and customs.; Rome -- History -- Julio-Claudians, 30 B.C.-68 A.D.; Italy -- History -- To 476.